Valuing immovable cultural heritage as opportunity generator for the revival of local identity. - Ivanc, Tjaša (2016)
Value is the center of heritage protection; it is what justifies legal regulations for protecting the built heritage and financial investments for its maintenance and suggests usefulness and benefits of the heritage as resource for regional growth and sustainability. Classifying (by means of proclamation) immovable property as being a part of monumental heritage has been the central instrument of heritage protection law. The basis of the protection is identifying the (object of) public interest, and this identification ex lege commences legal protection i.e. protection regimes are restored on proclaimed immovable monuments. Even though values are widely understood to be critical to understanding for heritage protection, there is a little knowledge how the whole range of values may be assessed in the context of decision-making and establishing significance of the build heritage in question. The paper seeks to examine the role of the built heritage as property development and its impact to local identity. A critical review of financial management and attitude of state and local government towards built heritage is undertaken.